Convenzioni concluse dagli Stati Membri e Diritto processuale civile internazionale dellUnione Europea: interpretazione conforme o rispetto degli obblighi internazionali? - Rossolillo, Giulia (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
According to articles 57 of the 1968 Brussels Convention on jurisdiction and enforcement of judgments in civil and commercial matters and 71 of the Council Regulation n. 44/2001, the Convention and the Regulation shall not affect any conventions to which the Member States are parties and which in relation to particular matters govern jurisdiction or recognition or enforcement of judgments. Although these rules are aimed to safeguard the obligations assumed by the Member States at international level, the Court of Justice seems to allow the application of the specialised conventions only insofar as they are consistent with the EU principles on judicial cooperation in civil matters.